2020
DOI: 10.1097/md.0000000000021681
|View full text |Cite
|
Sign up to set email alerts
|

The Risks of Exfoliative Esophagitis in Patients with Atrial Fibrillation

Abstract: The aging of the population has resulted in atrial fibrillation (AF) becoming increasingly prevalent. Treatment focuses on the prevention of thromboembolism through the use of catheter ablation or drug therapy with anticoagulants, such as warfarin or direct oral anticoagulants (DOACs). Dabigatran-induced exfoliative esophagitis has been reported as a rare side effect of DOACs. Although most cases are mild, some result in severe outcomes. However, the etiology of exfoliative esophagitis remains incompletely und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…1 Dabigatran is prescribed as a relatively large capsule (18-19 mm in length, 280-390 mg in weight), which can easily get lodged in the oesophagus. 2 It is reported that the size and weight of the capsule affect the oesophageal transit time, and capsules are more likely to adhere to the oesophageal mucosa compared with tablets. 2 3 Therefore, dabigatran has a tendency to get lodged in the oesophagus.…”
Section: Descriptionmentioning
confidence: 99%
See 4 more Smart Citations
“…1 Dabigatran is prescribed as a relatively large capsule (18-19 mm in length, 280-390 mg in weight), which can easily get lodged in the oesophagus. 2 It is reported that the size and weight of the capsule affect the oesophageal transit time, and capsules are more likely to adhere to the oesophageal mucosa compared with tablets. 2 3 Therefore, dabigatran has a tendency to get lodged in the oesophagus.…”
Section: Descriptionmentioning
confidence: 99%
“…2 3 Therefore, dabigatran has a tendency to get lodged in the oesophagus. 2 Dabigatran is the only DOAC containing the eluting tartaric acid core, which can cause oesophageal injury. 2 Because dabigatran can dissolve in a strongly acidic environment, it has tartaric acid as the core, which is coated with dabigatran etexilate.…”
Section: Descriptionmentioning
confidence: 99%
See 3 more Smart Citations